(untitled) (The Review of Diabetic Studies, 2024)
Objective: In the absence of a study of the applicability of postprandial lipid profiles in the Moroccan and Maghrebin population, we report a study comparing fasting and non-fasting lipid profile in a population of type 2 Moroccan diabetic. Our objective was to verify the applicability of postprandial lipid profiles in this population and secondarily determine the association of the non-fasting of lipid parameters with established cardiovascular disease. Patients and methods: In a prospective interventional before-and-after study, including type 2 Moroccan diabetic patients, aged over 18 years, received in endocrinology department of a tertiary care teaching hospital. Blood samples taken after a 12-hour fast were compared to those taken 2 to 3 hours after a standardized breakfast (postprandial test). The intraclass correlation coefficient (ICC) was used to compare the intraindividual lipid profiles. Results: 180 patients with Type 2 Diabetes Mellitus, were included in the study. The average age of patients was 59.42 ± 8.72 years with a male predominance (56.1%). The mean differences between non-fasting and fasting total cholesterol, high-density lipoprotein, triglycerides, low-density lipoprotein, and non-HDL-C were -0.04 g/L, -0.0 g/L, +0.33 g/L, -0.05 g/L, and -0.03 g/L, respectively. A good ICC correlation >75% was approved for all lipid fractions. There is no association between non-fasting lipid profile and established cardiovascular disease. Conclusion: Non-fasting lipid profiles were applicable in this population. They are more comfortable and convenient for our diabetic patients, allowing to reduce waiting times and avoid fasting-related hypoglycemia.